VD_FINDINFO HC / 2016 / 736 vom 9. Juni 2016 - VD Tribunal cantonal (2016)
LÉGITIMATION ACTIVE ET PASSIVE, REPRISE CUMULATIVE DE DETTE | 143 al. 1 CO, 175 CO, 181 CO, 125 let. a CPC (CH), 237 CPC (CH), 308 al. 1 let. a CPC (CH)